Analgesia Equina De Uso Común: Efectos Adversos Y Nuevas Alternativas Terapéuticas (2024)
In the case of horses, pain is a common and especially important clinical manifestation, which occurs in typical pathologies of the species such as equine colic, osteoarthritis and laminitis; as well as in postoperative and chronic stages of pain. The therapy associated with these conditions is based on the use of molecules with recognized adverse effects that could perpetuate, in certain conditions, the pain condition in patients.